(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
The presented work is conducted to examine the impact of hypercholestrolemic diet on male rabbits’ kidneys. A total of 10 male and adult rabbits have been divided (randomly) into 2 groups (5/group) for three months, while the first group was allowed to ad labium supply and drinking tap water and was termed as the control group (G1). Second group rabbits have orally administrated 1,5% gm of the cholesterol with the diet throughout the 3 months (G2). This work indicated the occurrence related to tissue changes in the kidney tissue compared with the control group. Conclusion: In conclusion, our study showed that the hypercholestrolemic diet at a dose of 1.5% gm caused pathological changes to the kidney tissue such as fatty changes in the tissue, the presence of fatty droplets within the capillary of the glomerulus, inflammatory infiltration of cells in the interstitial tissue of the kidney, cystic expansion of the renal tubules, and addition to the presence of hemorrhage compared to the control group